A GUERRA COMO PROBLEMA PARA OS ESTUDOS LITERÁRIOS - Ginsburg, Jaime (Organon, 2012)
when we try to articulate Aesthetics and Ethics, empathy might be a very important concept. In this essay, we consider how war and literature can be related, in Literary Studies. War is not only a theme, but also a formal issue. Literary genres, realism and images of death are examined as relevant aspects in this matter. According to Frankfurt School, we comment texts written by Guimarães Rosa and Sérgio Chejfec, explaining how they confront images of war coming from the tradition of classical epic and conventional realism.